Antidiabetic Activities In Vitro and In Silico of Nonpolar Compounds in Patat Leaves (Phrynium capitatum) - Wijayanti, Laras; Marvel, Marvel; Ma’arif, Samsul; Fathoni, Ahmad (EduChemia: Jurnal Kimia dan Pendidikan, 2024)
One form of Indonesian cultural wisdom is the use of leaves as food packaging. In addition to being used as a packaging material, patat leaves are also believed to have antidiabetic benefits. Antidiabetic activity can be assessed through the enzyme α-glucosidase inhibitory activities. In this research, an in vitro and in silico analysis of antidiabetic activity was conducted for the first time on nonpolar extracts of patat leaves. In vitro analysis was conducted using the α-glucosidase enzyme inhibition method, compound analysis was conducted using GC‒MS/MS, and an in silico study was conducted via the molecular docking method to the α-glucosidase receptor (PDB: 3W37). The results showed that the nonpolar extract (n-hexane) had very weak antidiabetic activity (with an IC50 >> 100 ppm). However, the sample inhibited α-glucosidase enzyme activity by up to 86.91%. GC‒MS/MS analysis confirmed the presence of 19 compounds in the nonpolar extract of the patat leaves. Straight-chain hydrocarbons dominate the compounds. The compound with the greatest abundance was Octadecyl 2,2,2-trifluoroacetate (RT 33.908; 9.53% area). An in silico test revealed that the compound with the greatest potential as an antidiabetic agent was γ-methylionone (40.78 μM). On the basis of the results of this theoretical approach, the compound can be further analyzed to validate its activity.